2020
DOI: 10.3390/ijms21196983
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does COA6 Play in Cytochrome C Oxidase Biogenesis: A Metallochaperone or Thiol Oxidoreductase, or Both?

Abstract: Complex IV (cytochrome c oxidase; COX) is the terminal complex of the mitochondrial electron transport chain. Copper is essential for COX assembly, activity, and stability, and is incorporated into the dinuclear CuA and mononuclear CuB sites. Multiple assembly factors play roles in the biogenesis of these sites within COX and the failure of this intricate process, such as through mutations to these factors, disrupts COX assembly and activity. Various studies over the last ten years have revealed that the assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Elucidating the biochemical function of these CcO assembly factors has remained a major bottleneck in our understanding of the biogenesis of CcO, with the role of COA6 in Cu A site formation being a case in point. A recent review article debated the potential role of COA6 as a metallochaperone or a thiol-disulfide oxidoreductase (disulfide reductase) in the copper delivery process [ 35 ]. Upon critical analysis of literature, we find that the current experimental data favors the disulfide reductase activity of COA6 and leads to a model where COA6 acts on its client proteins—COX2 and SCO1—by reducing the disulfide bond between their copper-coordinating cysteines to allow for copper binding ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elucidating the biochemical function of these CcO assembly factors has remained a major bottleneck in our understanding of the biogenesis of CcO, with the role of COA6 in Cu A site formation being a case in point. A recent review article debated the potential role of COA6 as a metallochaperone or a thiol-disulfide oxidoreductase (disulfide reductase) in the copper delivery process [ 35 ]. Upon critical analysis of literature, we find that the current experimental data favors the disulfide reductase activity of COA6 and leads to a model where COA6 acts on its client proteins—COX2 and SCO1—by reducing the disulfide bond between their copper-coordinating cysteines to allow for copper binding ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the human recombinant COA6 protein has been determined by both X-ray crystallography and nuclear magnetic resonance (NMR) spectroscopy. Both the structures show COA6 as a helical protein with coiled-coil-helix-coiled-coil-helix (CHCH) fold domain [ 24 , 35 , 36 ]. COA6 contains three α-helices where the first two helices—helix 1 (H1) and helix 2 (H2)—form a CHCH domain stabilized by two disulfide bonds between the cysteine pairs of its CX 9 C-CX 10 C motif ( Figure 3 a,b) [ 24 , 36 ].…”
Section: Structure Of Coa6mentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent studies have suggested that COA6 is a thiol-reductase binding SCO1 and/or SCO2 and catalyzing the reduction of critical Cys residues in SCO1 and/or SCO2 as well as MT-CO2 allowing the transfer and binding of Cu to MT-CO2 ( Soma et al, 2019 ; Pacheu-Grau et al, 2020 ). The exact COA6 binding partners and mechanisms are still not completely clear as the interpretation of the results varied in different laboratories depending on the experimental approach used ( Maghool et al, 2020 ).…”
Section: Redox-regulation Of Oxphos Components and Biogenesis Factorsmentioning
confidence: 99%
“…COX assembly factor 6 (COA6), a small intermembrane space-located protein, plays a role in the biogenesis of COX, as described in an interesting review by Maghool and coauthors [9], which discusses the current understanding of the molecular mechanisms by which COA6 participates in COX biogenesis. In particular, some evidence has indicated that COA6 binds copper, essential for COX assembly, activity, and stability; at the same time, COA6 possesses a thiol oxidoreductase activity, which could correlate with copper binding.…”
mentioning
confidence: 99%